2008
DOI: 10.1007/s12080-008-0012-6
|View full text |Cite
|
Sign up to set email alerts
|

Spillover from marine reserves related to mechanisms of population regulation

Abstract: Spillover of fish from marine reserves to adjacent harvested waters may be mediated by density-independent movement, density-dependent movement, or both. If dispersal is by random movement, populations within the reserve must be regulated by density-dependent population growth (DDG). Density-dependent movement (DDM) can also regulate the population if accelerated emigration from a reserve to the surrounding fishing grounds leads to substantially increased mortality. Using spatially explicit models, we show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 57 publications
(54 reference statements)
0
36
0
Order By: Relevance
“…Increased movement out of reserves with increased density can, theoretically, lead to increased spillover with increased reserve size (Kellner et al 2008), as opposed to the typical expectation of decreased spillover with increased reserve size because of greater retention. Conversely, increased movement into reserves can lead to greater within-reserve abundance and less spillover with greater movement rates , Langebrake et al 2012, as opposed to smaller movement rates as typically expected.…”
Section: Wwwannualreviewsorg • Responses To Marine Reserves 55mentioning
confidence: 88%
See 2 more Smart Citations
“…Increased movement out of reserves with increased density can, theoretically, lead to increased spillover with increased reserve size (Kellner et al 2008), as opposed to the typical expectation of decreased spillover with increased reserve size because of greater retention. Conversely, increased movement into reserves can lead to greater within-reserve abundance and less spillover with greater movement rates , Langebrake et al 2012, as opposed to smaller movement rates as typically expected.…”
Section: Wwwannualreviewsorg • Responses To Marine Reserves 55mentioning
confidence: 88%
“…However, declines can occur if the fishing effort displaced by reserves leads to increased mortality that outweighs the amount of spillover (Karnauskas et al 2011, Rassweiler et al 2012. Overall, the typical expected (Kellner et al 2008, Pelc et al 2010, White et al 2011 and observed (e.g., Hackradt et al 2014, Willis et al 2003) spatial distribution of abundance peaks within reserves and declines toward the reserve boundaries, depending on the spatial pattern of fishing in harvested areas (e.g., concentration of fishing effort near reserve boundaries; see Kellner et al 2007). The current standard for empirical inference of reserve-driven population responses is a before-after control-impact design-in other words, measurement of populations both inside and outside a reserve and before and after reserve establishment, which can control for the effect of environmental variability on population changes in time and the effect of habitat quality on population differences in space (Guidetti 2002, Jennings 2000.…”
Section: Response To Heterogeneity In Space and Timementioning
confidence: 96%
See 1 more Smart Citation
“…Kellner et al (2007Kellner et al ( , 2008 and Perez-Rusafa et al (2008) have previously shown that this form of a reaction-diffusion model produces the sigmoid shaped spillover curves exhibited across many marine reserve boundaries. Accordingly, population density, n, is described at each point in space as follows:…”
Section: Population Models (Reaction-diffusion Models)mentioning
confidence: 93%
“…Growing evidence from theoretical models and empirical studies suggests that higher abundances inside reserves can lead to spillover of adults to nearby fished areas (Rowley 1994;Roberts et al 2001;Goni et al 2008;Kellner et al 2008;Perez-Ruzafa et al 2008). Spillover is typically observed as declining patterns of abundance or catch across reserve boundaries, although there may be no detectable pattern of decline in abundance if fishing effort is intense surrounding the reserve.…”
Section: Introductionmentioning
confidence: 99%